How Multiple Organizational Changes Shape Managerial Support for Innovative Work Behavior: Evidence From the Australian Public Service - Wynen, Jan; Boon, Jan; Kleizen, Bjorn; Verhoest, Koen (Review of public personnel administration, 2020)
Public organizations were once seen as the epitome of stability and implacability. More recently, however, public organizations have been subject to fast-paced environmental change. One common response to the challenges posed by these volatile environments has been the adoption of various organizational changes to make public organizations more adaptable. However, following threat-rigidity theory, this study argues that as employees perceive multiple organizational changes, managerial support for innovative work behavior (IWB) of employees decreases. Analyses on the Australian Public Service (APS) employee census support these assertions. Our results contribute to the literatures on work behavior, organizational innovation, and human resources management, by demonstrating that multiple organizational changes negatively affect managerial support for IWB of individual employees, which may—through their negative impact on individual-level innovations—ultimately affect the very adaptability of organizations that many changes aspire to achieve.